Rede 5G: os benefícios, desafios, vulnerabilidades e segurança da quinta geração de redes móveis: as ameaças sobre a segurança e privacidade dos usuários - SANTOS, Luiz Felipe Capela (2023)
5G is the fifth generation of broadband cellular network technology that began to be deployed worldwide in 2019, broadly proposing several benefits and features that stand out with great difference from previous technologies. However, it is necessary to raise some questions about it. The security of this technology, as addressed in the 5G America report, published in July 2020: “security consideration for the 5G”, which was the reference that motivated the development of this work, resulting in some widely publicized points as characteristics and benefits of this technology, which oppose and equilibrate the balance of comparison between benefits and risks for users.